Strategi PT BRI Dalam Upaya Mendukung Kemajuan Pendidikan di Pulau Sebatik Nunukan Kalimantan Utara - Siti Qona'ah; Gan Gan Giantika (LPPM Universitas Bina Sarana Informatika, 2022)
Sebatik Island is located in the District of Nunukan Regency, North Kalimantan, whose territory is divided into two parts. Part of the territory is the territory of Malaysia and part of it belongs to the territory of the Republic of Indonesia. In border areas, people who have dual citizenship can affect the character and lifestyle of the local community and have a negative impact on border area security and a sense of nationalism. Regional border education is a very important thing to pay attention to. PT Bank Rakyat Indonesia implemented a strategy in overcoming these problems through the BRI Peduli CSR program, the CSR program strategy was implemented in the form of providing transportation facilities to Madrasah Tsanawiyah As'adiyah on the sebatik island of Nunukan, North Kalimantan. The purpose of this study is to describe PT BRI's Strategy in Supporting the Advancement of Education in Sebatik Island, Nunukan, and North Kalimantan. The methodology used is a qualitative methodology with a case study method through library research and observation data collection methods. The results showed that PT BRI's strategy through the BRI Peduli CSR program with the 3p concept, namely pro people, pro planet and pro profit Providing transportation facilities is very useful in helping students and students of Madrasah Tsanawiyah As'adiyah in traveling to school locations so that education can be carried out effectively. fluent and can print students or quality human resources